Seni Lukis Kaca Cirebon Refleksi Akulturasi Budaya - Cholis, Henri (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2009)
This research was an attempt to find out the existence of the painting style in Cirebon. The decision to choose the topic was based on the aims at having a good knowledge of glass painting for improving the subject of glass painting. Cirebon was chosen as the location for the research because glass painting had been the inseparable  part of the cultural history of the city. In the course of time, the glass painting of Cirebon had come up with its unique style or characteristics which deve-loped until the present day. The problem studied in this research was the existence of the painting and glass painting style of Cirebon. The style of  this research is description of a qualitative nature, and the study takes the form of a field study using an aesthetic approach.The results of the research show that the glass painting developing in Cirebon is the result of the cultural acculturation of Arab, China, Java and that the unique style elements  of fine arts come into existence. The painting objects such as padasan ( a kind of water jar with a spout for ritual cleansing), rain cloud, three fish with one head, macan ali, figures of wayang, calligraphic wayang, sunya ragi, Singo Barong are the themes as the reference for the artists of glass painting in Cirebon. However, the younger artists of glass painting develop painting style outside the traditional themes. The glass painting of Cirebon can survive because of the support of the government, the court, the artists, curators, gallery, and market. Key words: style, glass painting, Cirebon.